A case of complete tetraploidy in amniocentesis with normal karyotype in subsequent cordocentesis - Balkan, Mahmut; Fidanboy, Mehmet; İsi, Hilmi; Akbaş, Halit; Kalkanli, Sevgi; Alp, M. Nail; Budak, Turgay (Journal of Pediatric Genetics, 2012)
We report a case of complete tetraploidy in amniotic fluid culture obtained at 17 wk of pregnancy. Amniocentesis was performed in this pregnancy because of a high-risk maternal serum screening result and abnormal ultrasound findings. Amniotic fluid was cultured in two flasks. Growth was very slow in one culture with no growth in the other. Harvest was possible after 3 wk, which revealed tetraploidy in all studied plates. Subsequent cordocentesis was performed to confirm the diagnoses of amniocentesis. Chromosomal analysis of the cordocentesis revealed a normal karyotype with 46,XY. A healthy male infant was born at term. This case illustrates that abnormal karyotypes in poor growth cultures could be misleading and should be confirmed by another technique, such as cordocentesis.
Keywords: Amniocentesis; cordocentesis; prenatal diagnosis; tetraploidy